Saúde mental, personalidade e adequação social de médiuns espíritas - Fernandes, Rodrigo Scalia (2016)
Introduction: Anomalous experiences lived by spiritists mediums are object of interest of the transcultural psychiatry for the need to differentiate religious / spiritual experiences from pathological ones. Objective: Assessment of personality, religiosity, social adjustment and social demographic characteristics of spiritist mediums, a population that usually manifest psychotic and dissociative symptoms. Methods: This was an observational transversal study. We interviewed 81 mediums from spiritist centers in Uberlândia city (Brazil). Six scales were used: a social demographic questionnaire, the Cloninger’s Temperament and Character inventory (ITC), the Social Adjustment Scale Self-report (SAS), The Duke Religion Index (P-Durel) and the Self- Report Psychiatry Screening Questionnaire (SRQ). Results: Most of mediums were women (62.4%) of mean age 50.6 years and high educational level (64.6%). The mediums study Spiritism for an average of 30 years. On average mediums had good social adjustment (mean SAS = 1.8), high rates of Organizational Religiosity activities (ORA = 4.8), Non-organizational Religiosity Activities (NORA = 4.6) and Intrinsic Religiosity (IR = 13.8). Overall, 16 participants (18,5%), were screened positive for mental disorders. The participants scored low in Harm Avoidance (14.8) and high in Self-Directedness (32.9). Conclusion: This population of mediums is well socially adapted, has a low prevalence of common mental disorders and personality traits usually associated with lower risk of mental disorders.